Job Satisfaction in Pt Nitya Pariwisata Mandiri, Badung - Mahardika, I Putu Yana; Sudja, I Nengah; Landra, Nengah (The journal of contemporary issues in business and government, 2021)
This study aims to determine the effect of organizational culture and motivation on job satisfaction and its effect on employee performance at PT. Nitya Wisata Mandiri, Badung. The population used in this study were all employees of PT. Nitya Wisata Mandiri, Badung, which numbered 90 people. The data analysis technique used is Partial Least Square (PLS) using Smart PLS software. The results of this study indicate that organizational culture has a direct or indirect effect on employee performance. Motivation has an indirect effect on employee performance. Organizational culture has a positive and significant effect on job satisfaction. Motivation has a positive and significant effect on job satisfaction. Job satisfaction has a positive and significant effect on employee performance. So it is suggested that the company can continue to maintain the consistency of a good organizational culture, then the company is advised to design a motivation system that can reach all employees, and the company should always make job satisfaction a consideration in an effort to improve employee performance.